Latino Mennonites: civil rights, faith, and evangelical culture - Hinojosa, Felipe (Young Center books in Anabaptist & Pietist studies, 2014)
Cover; Contents; Preface; Acknowledgments; Abbreviations; Introduction: Interethnic Alliances, Sacred Spaces, and the Politics of Latino Evangelicalism; Part I: Missions and Race; CHAPTER 1. Building Up the Temple: Mennonite Missions in Mexican and Puerto Rican Barrios; CHAPTER 2. Missionary Motives: Race and the Making of the Urban Racial Council; Part II: Black, Brown, and Mennonite; CHAPTER 3. The Fight over Money: Latinos and the Black Manifesto; CHAPTER 4. "Jesus Christ Made a Macho Outta Me!": The 1972 Cross-Cultural Youth Convention.